A novel method to fabricate two-dimensional nanomaterial based on electrospinning. (April 2021) - Ji, Wenjing; Zhao, Guojie; Guo, Cong; Fan, Li; Deng, Hua; Du, Rongni; Fu, Mi; Sui, Guopeng; Fu, Qiang
Abstract: Two-dimensional (2D) nanomaterials have been widely used as advanced functional materials due to their special nanostructures and various functionalities. Researchers working on 2D nanomaterials are facing several problems, the difficulties in synthesis, scarcity of species, largely unclear formation mechanism and non-universal preparation method. Herein, this paper reports a new method based on electrospinning to fabricate 2D inorganic materials (titanium dioxide) with thickness around 20 nm and width/thickness ratio of >50. These 2D nanobelts TiO2 could enhance the dielectric performance of PVDF based composites much more significantly, and the energy density of 12.45 J/cm 3 could be easily achieved with a small volume fraction (3 vol%) of the nanobelts. Such method has many advantages such as safe production, low production cost, and continuous production. More importantly, this approach is potential to become a universal method to fabricate a range of 2D inorganic nanomaterials in the future due to its universality.